Bitcoin’s Crypto Currency: An Analysis from Operational Research and Information Management (2019)
Objective: This article focuses on an analysis that interrelates elements of information management with aspects of operations research, with the intention of demonstrating how the behavior of the Bitcoin crypto currency can be predicted. Methods/Statistical Analysis: Initially, Bitcoin crypto currency is characterized (price history, behavior in the market, variation over a period of time, etc.). Then, the data and information collected are applied to two techniques associated with operations research: Markov Chains and Queue Theory. Finally, the information that has emerged is transformed into valuable knowledge based on an information management process. Findings: This research demonstrates how techniques associated with operations research and information management (quantitative analysis and qualitative analysis) can be combined to characterize an object or process, capture data and information associated with it, predict its behavior and transform that information into a knowledge that generates added value, allowing the right decision making, in a specific context. In this way, it is possible to demonstrate how Bitcoin crypto currency is a really stable resource and an asset capable of supporting and transferring value in current and future markets, with a constant upward trend and a behavior very similar to that of conventional currency. Application/Improvements: This analysis establishes that no matter how complex or novel an object or process may be, it can be studied with tools such as these. The key is to implement them in other contexts